Late Paleozoic multi-stage subduction accretion of the southwestern Central Asian Orogenic Belt: insights from the Late Carboniferous-Early Permian granites in the southern West Junggar, NW China - Duan, Fenghao; Li, Yongjun; Zhi, Qian (International geology review, 2022)
The Late Carboniferous to Early Permian tectonic evolution of the South West Junggar (SWJ), northwest China, a crucial constituent in the southwestern domain of the Central Asian Orogenic Belt (CAOB), has long been the subject of debate. Here, detailed petrographic studies, new nine LA-ICP-MS zircon U-Pb ages and forty-nine whole-rock geochemical results from six granitic plutons in the SWJ were combined with previously available data to elucidate their petrogenesis and re-decipher Late Palaeozoic tectonic evolution and accretionary process of the southwestern CAOB. The studied granites can be geochemically classified as I- and A-type granites, and the former is further subdivided into I-type and highly fractionated I-type granites. The calc-alkaline I-type amphibole-bearing granites (Group I) yield crystallization ages of ca. 317-315 Ma, and exhibit depletions in HFSEs and enrichments in LILEs with no to slight Eu anomalies and low zircon saturation temperatures, indicating that the formation of these granites may be closely related to the subduction of the Junggar oceanic slab. The Group II granite porphyries (ca. 312 Ma) contain negligible amphibole, and are characterized by evolved SiO 2 but low zircon saturation temperatures with sharply negative Eu, Ba, Nb, Ta, Sr, P and Ti anomalies, belonging to highly fractionated I-type granites, and were probably produced in a tectonic transition from compressional to extensional setting. In contrast, the latest Carboniferous (ca. 304-298 Ma) alkaline A-type granites (Group III) are amphibole-absent, and are similar to Group II granites in major element compositions, but exhibit higher zircon saturation temperatures, indicating that they probably resulted in a back-arc extensional setting triggered by roll-back of the subducting Junggar oceanic slab since ca. 310 Ma. In combination with regional geology and re-interpretation of previous data, a multi-stage subduction-accretion model is suggested to account for the Late Palaeozoic tectonic evolution of the southwestern CAOB. This model can plausibly interpret the differences in duration of subduction between the northern and southern domains of West Junggar and the coexistence of A-type granites with subduction-related sanukites in the SWJ during Carboniferous to Permian.